A Generalized Benders Decomposition for Mixed-Integer Nonlinear Programming: Theory and Applications - Haq, Fadiah Hasna Nadiatul; Chaerani, Diah; Triska, Anita (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
This paper comprehensively explains how to solve mixed-integer nonlinear programming (MINLP) models using the generalized benders decomposition (GBD) method. The MINLP problem is an optimization model in which some variables must be integers and the objective function or constraints are nonlinear.  The GBD method is an extension of the Benders Decomposition (BD) method, effectively handles the characteristics of the MINLP  model, where the model has nonlinear properties and involves two types of variables, namely continuous variables and integer variables. The GBD method decomposes the problem into primal and master problems that are solved alternately until the optimal solution is found. The main difference between the GBD and BD methods is that GBD uses nonlinear duality in the main problem so that GBD can solve the nonlinear problem, whereas BD applies linear duality. This paper also presents some theorem proofs related to GBD that were not presented in detail in the previous literature. The application of the GBD method is also presented to demonstrate how the method can be effectively used to solve real-world MINLP problems.